Herd Immunity: A Major Advantage or A Major Challenge to Achieve for the COVID-19 Pandemic - Parisha Subhash Walinjkar (Indian Journal of Forensic Medicine & Toxicology, 2021)
COVID-19 caused by the novel SARS-COV2 has been causing worldwide panic in recent times. Globalepidemiological findings have shown numerous new cases being reported daily as well as drastic mortalityrates. It is the need of the hour to plan out strategies to cope with this ongoing pandemic. Herd immunityhas been used as an effective approach for years during epidemics and can prove to be a major advantage incontrolling the spread of the disease. Various models have been studied using mathematical estimates to findout how herd immunity can be achieved as well as to predict risks involved in doing so. The current scenariowhere there are no efficient vaccines available has also been taken into consideration. It is important to takeall these facts into consideration to come to a valid conclusion of whether achieving herd immunity can bebeneficial or impractical.